2007
DOI: 10.1021/bi7007382
|View full text |Cite
|
Sign up to set email alerts
|

Peptide and Small Molecules Rescue the Functional Activity and Agonist Potency of Dysfunctional Human Melanocortin-4 Receptor Polymorphisms,

Abstract: The melanocortin pathway, specifically the melanocortin-4 receptor and the cognate endogenous agonist and antagonist ligands, have been strongly implicated in the regulation of energy homeostasis and satiety. Genetic studies of morbidly obese human patients and normal weight control patients have resulted in the discovery of over 70 human melanocortin-4 receptor (MC4R) polymorphisms observed as both heterozygous and homozygous forms. A number of laboratories have been studying these hMC4R polymorphisms attempt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 81 publications
2
60
0
Order By: Relevance
“…In a recent study (Xiang et al 2007), distinct relative potencies versus a-MSH were observed for synthetic agonists depending on the mutated receptor as compared with wild-type hMC4R. In agreement with that work, differences in IRC-022493 and IRC-022511 potency depended on the mutation type, although in this study, the potency ratio of IRC-022493 or IRC-022511 versus a-MSH was unchanged in mutated hMC4R as compared to wild-type hMC4R.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In a recent study (Xiang et al 2007), distinct relative potencies versus a-MSH were observed for synthetic agonists depending on the mutated receptor as compared with wild-type hMC4R. In agreement with that work, differences in IRC-022493 and IRC-022511 potency depended on the mutation type, although in this study, the potency ratio of IRC-022493 or IRC-022511 versus a-MSH was unchanged in mutated hMC4R as compared to wild-type hMC4R.…”
Section: Discussionsupporting
confidence: 90%
“…hMC4R and the ligands. Except for Ser127Leu, they are positioned closer to the cytoplasmic side of the lipid bilayer and are likely to be involved in ligand-induced conformational changes important for G-protein-induced signal transduction events (Xiang et al 2007). Ser127Leu is located in the third transmembrane domain and was described to be an important residue for interacting with the endogenous melanocortin conserved His-Phe-Arg-Trp residues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…128 Numerous MC4-R agonists are being developed as potential targets for obesity therapy. [129][130][131] Other experimental drugs Several other medications are at different stages of investigation for their ability to induce weight loss and include: tesofensine (sympathomimietic), SIRT 1, peptide analog of growth hormone fragnment hGH 177-191, somatostatin, Axokine, Neuropeptide Y Receptor antagonists, pancreatic lipase inhibitor (cetilistat), cholecystokinin, beta3 adrenergic receptors agonists, and combination of anti-obesity drugs, in addition to multiple experimental drugs in early phase of development. 132 …”
Section: Oxyntomodulinmentioning
confidence: 99%